Mr. Putter & Tabby : Stir the soup - Rylant, Cynthia; Howard, Arthur (Orlando, Fla. : Harcourt, 2004)
Mr. Putter and Tabby go to their neighbor's house to make soup, but Zeke the dog makes it very difficult for them.
Booklist
Horn Book
School Library Journal
Booklist, July 2003
Christian Library, October 2003
Horn Book, April 2004
Keywords: Cats -- Fiction; Dogs -- Fiction; Neighbors -- Fiction; Putter, Mr. (Fictitious character) -- Fiction; Soups -- Fiction; Tabby (Fictitious character : Rylant) -- Fiction; Cats -- Fiction; Dogs -- Fiction; Neighbors -- Fiction; Putter, Mr. (Fictional character) -- Fiction; Soups -- Fiction; Tabby (Fictitious character : Rylant) -- Fiction